Effects of Welded Mechanical Heterogeneity on Interface Crack Propagation in Dissimilar Weld Joints - Fu-qiang Yang; He Xue; Ling-yan Zhao; Xiu-rong Fang (Advances in Materials Science and Engineering)
The stress and strain status associated with the material properties is one of the main factors affecting stress corrosion cracking (SCC) of structural components in nuclear power plants (NPPs). In many SCC prediction models, the stress intensity factor calculated with homogeneous materials is used to characterize the crack tip stress state. However, the mechanical and material properties in weld joints are heterogeneous, which will produce the discontinuous distribution of stress and strain nearby crack tip and affect the crack propagation. To understand the material mechanical heterogeneity effects on interface crack propagation, the specimens with ultimate tensile strength mismatch and elastic modulus mismatch were studied by using an extended finite element method (XFEM). The results indicate that the interface crack extension is easy to occur in the specimens with larger ultimate tensile strength mismatch, while the elastic modulus mismatch has little effects on crack extension. The different interface cracks in the dissimilar metal weld joints of the reactor pressure vessel used in NPPs tend to deviate from the initial direction into alloy 182, and the interface crack propagation path fluctuation is small.